DISTRIBUTION AND ROLE OF RHYHNOCORIS IRACUNDUS (HETEROPTERA: RE-DUVIIDAE) IN BIOLOGICAL CONTROL IN THE FERGANA VALLEY (Scientific journal of the Fergana State University, 2026)
This article examines the distribution, ecological characteristics, and the role of Rhynocoris iracundus (Heteroptera: Reduviidae) in biological control of agricultural pests under the conditions of the Fergana Valley. The research was conducted during 2020–2024 in agroecosystems of field crops. The results showed that R. iracundus occurs in various biotopes, and its main prey includes representatives of the families Pentatomidae, Miridae, Aphididae, and Thripidae. The seasonal dynamics of the species are associated with the increase in pest populations, and as a natural entomophage, it plays an important role in maintaining balance within agroecosystems.